Join sheet Metal with cold-Extruded Pins - Römisch, David (Assembly, 2024)
Lightweight structures and multi-material assemblies are of great interest to the automotive industry. However, joining dissimilar materials poses a challenge. Conventional joining methods, such as welding, bonding, screwdriving and riveting, have limited effectiveness due to differences in stiffness, chemical compatibility and thermal expansion. A new mechanical joining method, using pin structures formed in one of the parts, has shown promise for assembling dissimilar materials.
CRIS-Team Scopus Importer:2024-12-13